Characteristics and propagation of switching-induced stress waves in SiC MOSFET power modules - Huang, Siqi; Fan, Lu; Heng, Qian; Ni, Qi; Sun, Meng; Mao, Yinke (Frontiers in Energy Research, 2025)
Switching-induced stress waves (SSW) are recognized as a promising non-invasive technology for real-time monitoring of power module packaging failures, though limited by the lack of a comprehensive understanding of their characteristics and propagation mechanisms. In this study, a dedicated SSW detection platform was developed for SiC MOSFET power modules, where the mechanical wave nature was verified through time-delay analysis. Dominant frequency components at 150 kHz and 270 kHz were identified using both piezoelectric ceramic and PVDF sensors. Experimental investigations further demonstrated that the time-domain parameters of SSW were predominantly influenced by bus voltage (UDC), followed by load current (IR), whereas principal frequency components remained stable across operational conditions. Propagation effects through the module were systematically analyzed via finite element modeling, revealing a 5.82% increase in signal amplitude and 5.88% spectral bandwidth expansion after transmission. These results confirm that sensor-captured signals can be effectively equated to original chip vibrations in defect-free propagation paths.